Inheritance Law in the African Legal System of Somalia, Nigeria, and Ghana - Asrianti Sukirman; Oyo Sunaryo Mukhlas (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Inheritance law is an important aspect of legal systems in various African countries. This research aims to analyze the differences and similarities in the system of inheritance law in three African countries, namely Somalia, Nigeria, and Ghana. Through a comparative law approach, this study describes various aspects of inheritance law, such as fundamental principles, inheritance of property, and inheritance rights in these three countries. This research employs a descriptive research method by analyzing relevant legal documents, including constitutions, laws, and court judgments related to inheritance law. Additionally, the study also includes a literature review on cultural, religious, and customary views that influence the system of inheritance law in Somalia, Nigeria, and Ghana. The findings of this research indicate significant differences in inheritance law among the three countries. Somalia implements an inheritance law system based on Islamic Sharia, with principles governed by Islamic law that involve a balance between male and female family members. On the other hand, Nigeria has an inheritance law system influenced by Islamic, Christian, and customary laws. Meanwhile, Ghana adopts an inheritance law system based on principles of customary law and local customs